On Gin Lane - Foster, Brooke Lea (Gallery Books, 2022)
"From the author of Summer Darlings, another page-turning historical novel about a debutante whose entire future is called into question after her fiancé's Hamptons hotel mysteriously burns down during its opening weekend in the summer of 1957"--